Energy absorption of thin-walled cylinders filled with silicone rubber subjected to low-velocity impact - Tadaharu ADACHI (The Japan Society of Mechanical Engineers, 2017)
In this paper, the effects of subjecting a thin-walled cylinder filled with silicone rubber to low-velocity impact on energy absorption were clarified on the basis of the results of drop weight testing and theoretical analysis. Aluminum alloy cylinders filled with silicone rubber with different hardnesses were prepared as specimens for the drop weight testing with an impact velocity of up to 5.5 m/s to measure the impact load-deformation relation. The analysis was conducted with elastic-perfectly plastic solid mechanics. The absorbed energy per unit deformation, namely the average load, was found to increase significantly due to filling the cylinders with rubber since the plastic deformation occurred in the whole cylinder due to radial expansion of the rubber during dynamic compression. The average load of the filled specimen was more than double that of the empty cylinder. Even though the cylinder fractured after the impact energy exceeded the capacity of the cylinder, high strength rubber could be utilized to support the impact load as a fail-safe. Therefore, it was clarified that the rubber inside the thin-walled cylinder contributed to increase the energy absorption and support the impact load as a fail-safe after the cylinder fractured.